Penyisihan, Warna, Zat Organik Dan Kekeruhan Pada Air Gambut Dengan Kombinasi Proses Koagulasi-Flokulasi Menggunakan Koagulan Poly Alumunium Chloride (PAC) Dan Membran Ultrafiltrasi - Zella Sri Rizka; Syarfi Daud; Syamsu Herman (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Generally, peat water quality not suitable with water quality standards Permenkes No. 416 / Menkes / Per / IX / 1990. Peat water treatment commonly used to produce treated water still above the quality standard. One of the peat water treatment methods used in this study is combination of coagulation-flocculation and ultrafiltration membrane. This study aims to determine the effect of coagulants Poly Aluminum Chloride (PAC) to decrease colour, organic matter and turbidity, determine the performance of membrane for flux and rejection of colour, organic matter, and turbidity with and without pre-treatment of coagulation flocculation, determine decrease of colour, organic matter, and turbidity in peat water treatment using ultrafiltration membrane with pre-treatment of coagulation-flocculation. Peat water treatment by flocculation and coagulation combination of ultrafiltration membrane using Poly Aluminum Chloride (PAC) as coagulant with dose 150 mg / L, and varying the ultrafiltration membrane feed pressure of 0.5; 1 and 1.5 bar. The result showed that the peat water treatment by combination of coagulation-flocculation and ultrafiltration membrane rejection coefficient values of color, organic matter and turbidity, the highest obtained at the pressure of 0.5 bar, with rejection coefficient values for color, organic matter and turbidity, respectively amounting to 98.72%, 92.54% and 100%. The best average flux value with pre-treatment of coagulation flocculation obtained at pressure 1.5 bar that is 275.400 L / m2.jam.Keywords: Coagulation-Flocculation, Colour, Organic Matter, Peat Water, Poly Aluminium Chloride (PAC), Turbidity, Ultrafiltration Membrane